A New All-Season Passive Sampling System for Monitoring H2S in Air - Hongmao Tang; James Sandeluk; Linda Lin; J. WIlliam Lown (The Scientific World Journal)
A new Maxxam All-Season Passive Sampling system for monitoring H2S in air has been developed. This passive sampling system employs the same approaches as the Maxxam All-Season Passive Sampling Systems for monitoring SO2, NO2, and O3 reported previously. This system has been extensively tested in the lab (temperature from -20 to 20°C, relative humidity from 30 to 84%, and wind speed from 0.5 to 150 cm/s) and validated in field studies. Comparing measurements obtained with the use of the new passive sampling system with equivalent measurement with the use of an active filter pack H2S sampler yielded an accuracy of greater than 85%. The new H2S passive sampling system can be used to measure ambient H2S concentrations ranging from 0.02 to 7 ppb based on a 1-month exposure period. There is no significant interference found from other sulfur compounds in air. This system has been used in many air monitoring projects.